A New Targeted Model of Experimental Autoimmune Encephalomyelitis in the Common Marmoset. (22nd September 2015) - Stassart, Ruth Martha; Helms, Gunther; Garea‐Rodríguez, Enrique; Nessler, Stefan; Hayardeny, Liat; Wegner, Christiane; Schlumbohm, Christina; Fuchs, Eberhard; Brück, Wolfgang
Abstract: Multiple sclerosis (MS) is the most common cause for sustained disability in young adults, yet treatment options remain very limited. Although numerous therapeutic approaches have been effective in rodent models of experimental autoimmune encephalomyelitis (EAE), only few proved to be beneficial in patients with MS. Hence, there is a strong need for more predictive animal models. Within the past decade, EAE in the common marmoset evolved as a potent, alternative model for MS, with immunological and pathological features resembling more closely the human disease. However, an often very rapid and severe disease course hampers its implementation for systematic testing of new treatment strategies. We here developed a new focal model of EAE in the common marmoset, induced by myelin oligodendrocyte glycoprotein (MOG) immunization and stereotactic injections of proinflammatory cytokines. At the injection site of cytokines, confluent inflammatory demyelinating lesions developed that strongly resembled human MS lesions. In a proof‐of‐principle treatment study with the immunomodulatory compound laquinimod, we demonstrate that targeted EAE in marmosets provides a promising and valid tool for preclinical experimental treatment trials in MS research.